Uji Total Plate Count (TPC) Bakteri Pada Minuman Teh Poci Homemade di Gampong Batoh Banda Aceh - Yuni Dewi Safrida; Hardiana Hardiana; Mauliyana Mauliyana (Fakultas Teknik, 2021)
Poci tea is a favorite beverage produced by household industry. Considering its hygienic quality so that it is not contaminated by microbes seems to be an important factor. This study aims to determine the level of microbial contamination in Poci tea produced by household retailers in Batoh, Banda Aceh. This study was conducted at the Pharmacy Laboratory, Academy of Pharmacy and Food Analysts (AKAFARMA) Banda Aceh from 8 to 12 June 2020. The method of this study is a quantitative experimental laboratory with Total Plate Count (TPC). The samples of this study are seven Poci tea obtained from Batoh retailers selected by random sampling. The results showed that the seven Poci teas samples were contaminated microbes, i.e ALMK with a TPC value of 4x103 colonies / ml, AMK with a TPC value of 4x103 colonies / ml, HFK with a TPC value of 2x103 colonies / ml, JLM with a TPC value of 3x103 colonies / ml, KUCB with a TPC value of 4x103 colonies / ml, MHFK with a TPC value of 4x103 colonies / ml, and MHZZ with a TPC value of 2x103 colonies / ml. In conclusion, the seven Poci tea samples sold in Batoh have TPC values that are not permitted by the Regulation of the Head of RI POM No. 16 of 2016. Therefore, this poci tea is not recommended for consumption.